2020
DOI: 10.19087/imv.2020.9.6.940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Ascaris Suum Infectionin Pigs in the Lowlandarea of Bali Province

Abstract: Cacing Ascaris suum merupakan parasit saluran cerna pada babi yang dapat menimbulkan gangguan kesehatan berupa kekurusan, diare, penurunan produktivitas ternak dan kerugian ekonomi yang besar. Cacing A. suum bersifat zoonosis. Tujuan penenelitian ini adalah untuk mengetahui prevalensi dan faktor risiko infeksi cacing A. suum pada babi di dataran rendah Provinsi Bali. Jumlah sampel yang digunakan sebanyak 200 sampel feses babi segar yang diambil dari wilayah dataran rendah basah dan rendah kering. Sampel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, the prevalence of all STH coinfections on the same farm had a prevalence of 0.84%, which was higher than what was observed in a previous study involving a lowland pig farm in Bali, which found an 18% prevalence of Ascaris spp. [ 66 ]. Meanwhile, the prevalence of hookworm was consistent with another study [ 67 ], where the prevalence was found to be 71% in lowland pig farms and 60% in Bali Province [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the prevalence of all STH coinfections on the same farm had a prevalence of 0.84%, which was higher than what was observed in a previous study involving a lowland pig farm in Bali, which found an 18% prevalence of Ascaris spp. [ 66 ]. Meanwhile, the prevalence of hookworm was consistent with another study [ 67 ], where the prevalence was found to be 71% in lowland pig farms and 60% in Bali Province [ 37 ].…”
Section: Resultsmentioning
confidence: 99%